2020
DOI: 10.1021/acscatal.0c01069
|View full text |Cite
|
Sign up to set email alerts
|

Role of Water on the Structure of Palladium for Complete Oxidation of Methane

Abstract: Palladium-based catalysts are attractive for methane combustion on natural gas vehicles at low temperature. By means of ambient pressure x-ray photoelectron spectroscopy, we investigated the reaction on a palladium foil exposed to different mixtures at increasing temperature. Water affects the long-term catalyst stability and blocks the active sites, ascribed to the hydroxyl inhibition effect. We investigated such an effect both under steady state and under transient reaction conditions, to understand the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 72 publications
(234 reference statements)
4
85
1
Order By: Relevance
“…However, in a recent study by Li et al ambient-pressure X-ray photoelectron spectroscopy was used to show that water addition to a Pd foil at 350-600°C leads to build-up of surface hydroxyls (and not palladium hydroxide) that block the methane dissociation and delay formation of active PdO. [51] Our results for realistic supported catalysts are in many respects analogous. Water addition impacts the dissociation of both CH 4 and O 2 , i. e., hampers the redox dynamics of the palladium particles, and seems to prevent lattice oxygens to take part in the methane oxidation reaction.…”
Section: Sample Idmentioning
confidence: 49%
“…However, in a recent study by Li et al ambient-pressure X-ray photoelectron spectroscopy was used to show that water addition to a Pd foil at 350-600°C leads to build-up of surface hydroxyls (and not palladium hydroxide) that block the methane dissociation and delay formation of active PdO. [51] Our results for realistic supported catalysts are in many respects analogous. Water addition impacts the dissociation of both CH 4 and O 2 , i. e., hampers the redox dynamics of the palladium particles, and seems to prevent lattice oxygens to take part in the methane oxidation reaction.…”
Section: Sample Idmentioning
confidence: 49%
“…The addition of 2 vol % of H 2 O to the feed shifted the temperature of 50 % methane conversion (T 50 ) on Pd(2)/(500C)CeO 2 to the higher temperature by 60 °C (Figure 4a). The presence of H 2 O in the feed has been reported to hamper the methane oxidation activity of catalysts by suppressing the oxygen mobility of support and by forming the catalytically less active Pd(OH) x species on PdO x surface [5e,6b,15a,17] . In addition, the methane oxidation activities of Pd(2)/(500C)CeO 2 and Pd(2)/(800C)CeO 2 catalysts were similar when H 2 O is present in the feed (Figure 4b).…”
Section: Resultsmentioning
confidence: 94%
“…Studies demonstrated that the methane-oxygen cyclic operation was not necessary to obtain high selectivity [60,61]. The active oxygen species responsible for the catalytic conversion of methane into oxygenated products has to be clarified because the reaction could proceed either in the gas phase through a chain propagation mechanism [62][63][64] and/or on the catalyst surface [58,[65][66][67].…”
Section: Non-faradaic Methane Oxidationmentioning
confidence: 99%
“…Gaseous methane first binds to the metallic sites [61], then hydrogen atoms are gradually abstracted by the adjacent surface M-O sites and yield M-OH. The reverse reaction of hydroxyl recombination is favored by H2O [6,37,61,64,68,69].…”
Section: Non-faradaic Methane Oxidationmentioning
confidence: 99%
See 1 more Smart Citation